Low-dimensional heteroatom-doped carbon nanomaterials prepared with thermally removable templates for the electrocatalytic reduction of oxygen. (March 2019) - Zhao, Dengke; Zhu, Xiaojing; Wang, Nan; Lu, Bingzhang; Li, Ligui; Chen, Shaowei
Abstract: Low-dimensional heteroatom-doped carbon nanomaterials represent a promising low-cost alternative to the conventional noble metal-based catalysts towards oxygen reduction reaction (ORR), a key process at the cathodes of fuel cells and metal-air batteries. It has been found that the electrocatalytic activity depends on the effective surface area and porosity, which dictate the accessibility of the catalytic active sites and mass transfer involved in the reaction. Toward this end, thermally removable templates have been used extensively in the preparation of a range of low-dimensional heteroatom-doped porous carbon nanomaterials that exhibit remarkable electrocatalytic activity towards ORR. In this article, we will summarize recent progress in this area of research and conclude with a perspective of the challenges and opportunities in future research. Graphical abstract: Image 1 Highlights: Oxygen reduction reaction (ORR) is an important process in diverse electrochemical energy technologies. Mesoporous doped carbons exhibit apparent electrocatalytic activity towards ORR. Thermally removable templates facilitate the pyrolytic formation of porous carbon. Removable templates such as zinc and iron compounds, SiO2, Te, and C3 N4 have been used.